PERAN KOMPETENSI SOSIAL GURU DALAM MENCIPTAKAN EFEKTIFITAS PEMBELAJARAN - Novianti Muspiroh (Edueksos : Jurnal Pendidikan Sosial & Ekonomi, 2015)
AbstractSocial competency is an important aspect for teachers in making effective learning. It can provide opportunities for students to undertake positive activities that can improve performances. Powered by good communication, the teacher will be more easily conveying a variety of information in particular lessons to be taught to students. In reality, however, social competence in learning is still overlooked by teachers, as it is often found in the learning process suggests that the interaction of teachers and students who are less effective and efficient, teachers who behave immorally and violencely. So, it is difficult to achieve effective learning. Therefore, social competence is very important for teachers. For that, teachers should improve it with effective communication, discussion and direct visitation to the community, training related to social competence, deepen knowledge of human relations, mastering social psychology, and adaptation to work in places. Key words:competency, social, efektiveness, learning